THE INFLUENCE OF MOTIVATION AND DIRECTION FUNCTION ON EMPLOYEE WORK DISCIPLINE IN THE DEPARTMENT OF TOURISM AND CULTURE OF SOUTH OKU DISTRICT - Helisia Margahana (DIA: Jurnal Administrasi Publik, 2020)
This research study aims to partially and jointly analyze the influence of Motivation, Guidance Function on employee work discipline, and to analyze the most dominant variables in influencing employee work discipline at the Office of Tourism and Culture of South OKU Regency. Results of regression analysis and the correlation between motivation and discipline Employee employment shows a regression model ? = 3.987 + 0.958X1 + e with a correlation coefficient of 0.900. The results of the regression analysis and the correlation between direction on employee work discipline show the regression model ? = 16,805 + 0.665X2 + e with a correlation coefficient of 0.825. The results of multiple regression analysis and the correlation between motivation and direction together on work discipline show the regression model ? = 2.817 + 0.675X1 + 0.300X2 + e with a correlation coefficient of 0.937 at the 95% confidence level, it is found that motivation and direction can simultaneously predict employee work discipline. Motivation and direction simultaneously have a strong positive effect with work discipline of 86.9% and have a significant effect. The effect of motivation and direction simultaneously on the work discipline of the employees of the South OKU Regency Tourism and Culture Office is 2,817, so if there is an increase in motivation and direction together then this will increase the work discipline of the OKU Regency Tourism and Culture Office employees South with significant .. This research was conducted on 28 respondents with the analytical method used is path analysis using SPSS software.